2006
DOI: 10.1021/ac060875h
|View full text |Cite
|
Sign up to set email alerts
|

δ34S Measurements of Sulfur by Multicollector Inductively Coupled Plasma Mass Spectrometry

Abstract: An accurate and precise method for the determination of delta34S measurements by multicollector inductively coupled plasma mass spectrometry has been developed. Full uncertainty budgets, taking into consideration all the uncertainties of the measurement process, have been calculated. The technique was evaluated by comparing measured values with a range of isotopically enriched sulfur solutions prepared by gravimetric addition of a 34S spike. The gravimetric and measured results exhibited a correlation of R2 >0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
82
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(88 citation statements)
references
References 30 publications
(39 reference statements)
5
82
0
Order By: Relevance
“…ICP-MS instruments are compatible with numerous sample introduction schemes, including solution (bulk) analysis and laser-ablation (in situ) analysis, which are not available for other techniques. ICP-MS represents a promising technique for the analysis of sulfur isotopes at sample masses (~ 10 µg S) similar to other techniques (Menegário et al, 1998;Mason et al, 1999;Prohaska et al, 1999;Krupp et al, 2004;You and Li, 2005;Clough et al, 2006;Mason et al, 2006). Measurement of S isotopes by single-collector ICP-MS is obtained sequentially and vriability of plasma conditions (e.g., efficiency of ionization, ion beam extraction) can significantly degrade the measurement of isotope ratios.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…ICP-MS instruments are compatible with numerous sample introduction schemes, including solution (bulk) analysis and laser-ablation (in situ) analysis, which are not available for other techniques. ICP-MS represents a promising technique for the analysis of sulfur isotopes at sample masses (~ 10 µg S) similar to other techniques (Menegário et al, 1998;Mason et al, 1999;Prohaska et al, 1999;Krupp et al, 2004;You and Li, 2005;Clough et al, 2006;Mason et al, 2006). Measurement of S isotopes by single-collector ICP-MS is obtained sequentially and vriability of plasma conditions (e.g., efficiency of ionization, ion beam extraction) can significantly degrade the measurement of isotope ratios.…”
mentioning
confidence: 99%
“…The introduction of multiple collector ICP-MS technology has enabled simultaneous measurement of multiple isotopes, providing precise and rapid isotope ratio determination. Precision better than 1 ‰ is now obtainable for δ 34 S isotope ratios (Clough et al, 2006;Mason et al, 2006). Implicit in the accurate and precise determination of isotope ratios by MC-ICP-MS is an appropriate correction for instrumental mass discrimination.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Typical applications include age determinations based on parent/daughter decay series such as U/Pb [126], U/Th [127], or Sr isotopes [128]. Other investigations study isotope fractionation by natural processes (e.g., S, Fe, and Os) [16,129,130] or for discriminating sample populations based on the isotope signature of characteristic elements (e.g., Sr in teeth and bones) [131,132].…”
Section: Isotope Ratio Determinationmentioning
confidence: 99%
“…Clough et al demonstrated that the isotopic analysis of S using a MC-ICP-SFMS instrument, operated at higher mass resolution, can be used for distinguishing counterfeit Viagra pills (the active component of which, sildenafil, is a S-containing molecule) from the genuine product. 270 Sample introduction was accomplished via laser ablation and was thus less time-consuming and labour-intensive compared to that required for gas source isotope ratio MS. Also counterfeit products of the antiviral drug Heptodin could be identified on the basis of Mg isotope ratio measurements carried out by MC-ICP-SFMS and complemented by gas source MS data. 271 …”
Section: Biological Samplesmentioning
confidence: 99%